KEDUDUKAN BADAN AMIL ZAKAT NASIONAL (BAZNAS) DALAM PERSPEKTIF KONSTITUSI INDONESIA - Muhammad Yasin Ardhy; Baihaki Baihaki (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2016)
Implementation or enforcement of Law No. 23 of 2011 provides authority to BadanAmil Zakat Nasional (Baznas) and Baznas Provincial / Municipal and ZakatManagement Unit (UPZ) as an institution that has the right to manage zakat ortreasury. BAZNAS role with regard to the implementation or enforcement of LawNo. 23 of 2011, carried out with the collection, distribution, utilization andreporting charity. Based on the research that is already quite large Baznas role inthe management of zakat in Indonesia.